2014
DOI: 10.1016/j.exphem.2014.07.269
|View full text |Cite|
|
Sign up to set email alerts
|

Disruption of the potassium channel regulatory subunit KCNE2 causes iron-deficient anemia

Abstract: Iron homeostasis is a dynamic process that is tightly controlled to balance iron uptake, storage, and export. Reduction of dietary iron from the ferric to the ferrous form is required for uptake by solute carrier family 11 (proton-coupled divalent metal ion transporters), member 2 (Slc11a2) into the enterocytes. Both processes are proton dependent and have led to the suggestion of the importance of acidic gastric pH for the absorption of dietary iron. Potassium voltage-gated channel subfamily E, member 2 (KCNE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
1
7
0
2
Order By: Relevance
“…It is likely, as with Long QT syndrome, that given enough time and patients, KCNE2 polymorphisms associated with at least subclinical hypochlorhydria will emerge, and possibly rarely associate with familial gastric cancer particularly if homozygous recessive cases of KCNE2 loss-of-function mutations occur (as is observed for hearing loss in LQTS patients with KCNE1 mutations and Jervell and Lange-Nielsen syndrome). We also discovered, unsurprisingly because low gastric pH is required for efficient iron absorption, that Kcne2 −/− mice exhibit iron-deficiency anemia 47 , a finding later confirmed by others 51 . Again, it will be of interest to see whether human KCNE2 polymorphisms, as with KCNQ1, correlate with anemia.…”
Section: Kcne2 In the Stomachsupporting
confidence: 73%
“…It is likely, as with Long QT syndrome, that given enough time and patients, KCNE2 polymorphisms associated with at least subclinical hypochlorhydria will emerge, and possibly rarely associate with familial gastric cancer particularly if homozygous recessive cases of KCNE2 loss-of-function mutations occur (as is observed for hearing loss in LQTS patients with KCNE1 mutations and Jervell and Lange-Nielsen syndrome). We also discovered, unsurprisingly because low gastric pH is required for efficient iron absorption, that Kcne2 −/− mice exhibit iron-deficiency anemia 47 , a finding later confirmed by others 51 . Again, it will be of interest to see whether human KCNE2 polymorphisms, as with KCNQ1, correlate with anemia.…”
Section: Kcne2 In the Stomachsupporting
confidence: 73%
“…The disruption of this regulatory subunit may also alter the levels of potassium in IDA. [4] This implies that IDA and serum potassium levels are interrelated with each other. Studies have revealed that electrolyte level alterations also occur in other types of anemia like sickle cell anemia and β-thalassemia.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Iron is vital for human health and defects in iron homeostasis result in serious pathologic abnormalities such as hemochromatosis and anemia. [4] ID is the world's most widespread nutritional disorder, irrespective of age, gender, and socioeconomic status, affecting both industrialized and developing countries. In ID , there is insufficient iron to maintain normal physiologic functions.…”
Section: Introductionmentioning
confidence: 99%
“…Kcne2 deletion-linked achlorhydria 24 causes iron-deficiency anemia 12 30 , which can predispose to dyslipidemia and NAFLD 11 . Although data vary depending on the animal model studied, iron deficiency in rats, for example, has been reported to increase hepatic lipogenesis, causing steatosis; this may occur via increased de novo lipogenesis from glucose 31 .…”
Section: Resultsmentioning
confidence: 99%